Academic experience satisfaction of pharmacy and dentistry students - Bueno, Julia Lucio [UNESP]; de Campos, Lucas Arrais [UNESP]; Peltomäki, Timo; Marôco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (International Pharmaceutical Federation (FIP), 2022)
Objective: To assess the psychometric properties of the Academic Experience Satisfaction Scale (ESEA) applied to Pharmacy and Dentistry students and investigate the effect of demographic and course-related characteristics on the ESEA factors. Methods: This was a cross-sectional study. Academic satisfaction was assessed by the ESEA. Construct validity was measured by confirmatory factor analysis (CFI, TLI, RMSEA). The composite reliability (CR) and the ordinal α were estimated. Structural model was elaborated considering demographic and course-related characteristics as the independent variable and ESEA factors as the dependent variables. The model fit and path estimates significance (β) were evaluated (z test; α = 5%). Results: 544 students participated in the study (70.0% female; mean age: 21.4 ± 2.4 years; 52.4% dental students). ESEA showed adequate fit to the data (CFI = 0.90; TLI = 0.90; RMSEA = 0.064, CR and α ≥ 0.88). In general, students reported being satisfied with their academic experience. Dental students and those from the first and second years of the course showed greater satisfaction with the academic experience. Sex did not have a significant impact on any of the scale's factors. Conclusion: ESEA produced valid and reliable data. Course-related characteristics, but not demographic characteristics, significantly affected the academic experience of students.
Keywords: Academic experience; Student; Validamon study